Peran Mahasiswa MSIB Batch 4 dalam Membangun Ekosistem Inovasi dan Entrepreneur Melalui Kompetisi Penjaringan Startup dan UMKM di PT Gama Inovasi Berdikari - Ninda Amaliatus Dwiana; Siti Ning Farida (Jurnal Informasi Pengabdian Masyarakat, 2023)
As we know, the increasingly massive digital disruption is certainly a challenge as well as an opportunity for startups in starting their business. Therefore, as a university-based accelerator company, PT Gama Inovasi Berdikari continues to strive to develop the company and help assist startups through various innovations to improve their business, one of which is by organizing a startup and MSME screening competition event through the Gama Inovasi Startup Summit 2023. The program, which is run from the role of Student Internship and Certified Independent Study (MSIB) Batch 4 PT Gama Inovasi Berdikari, especially by the Innovation Program subdivision from March - June 2023, runs in parallel with on-site internship activities. The results achieved by startups and MSMEs responded positively to this activity which later could create a productive ecosystem for startups selected in the acceleration and incubation program.